Background of the landscape in Peru. Scientific view and production of images of the Peruvian territory during the 19th century - Cárdenas Claux, Nicolás (2025)
During the 19th century in Peru, some representations of the national territory were developed, and although scarce, contributed to the creation of a visual imaginary about the territory that lasts to this day. Unlike other Latin American countries such as Ecuador, Brazil or Chile, whose first representations came from landscape painting, in Peru these images were created from other disciplines such as geography and photography. These representations were both a product and a disseminator of an ideological stance towards nature and territory typical of the scientific discipline and the prevailing prejudices at that time. Furthermore, it created and disseminated among the population, the elites and the state apparatus an imaginary about the national territory divided into 3 geographical zones separated by the Andes mountain range, which, from the point of view of the coastal inhabitant, stands as a barrier to national development.